Metal-free melem/g-C3N4 hybrid photocatalysts for water treatment - Liu, S.; Sun, Hongqi; O'Donnell, Kane; Ang, Ming; Tade, Moses; Wang, Shaobin (2016)
© 2015 Elsevier Inc. In this study, graphitic carbon nitride was engineered to produce metal-free melem/g-C3N4 hybrid photocatalysts through a hydrothermal technique. It was revealed that the hydrothermal treatment of g-C3N4 could produce a hybrid structure of "thorn ball" liked melem on g-C3N4 layer at a high temperature, and was able to modify the photoelectronic properties of g-C3N4. The spectroscopic measurements implied that a melem/g-C3N4 hybrid has better light absorption and lower electron/hole recombination than pristine g-C3N4. Therefore, the melem/g-C3N4 photocatalysts can decompose methylene blue solution under artificial sunlight with a higher rate and also present good stability.